Anti-TNF Therapy Is Associated With an Increased Risk of Postoperative Morbidity After Surgery for Ileocolonic Crohn Disease: Results of a Prospective Nationwide Cohort. Issue 2 (February 2018) - Brouquet, Antoine; Maggiori, Léon; Zerbib, Philippe; Lefevre, Jérémie H.; Denost, Quentin; Germain, Adeline; Cotte, Eddy; Beyer-Berjot, Laura; Munoz-Bongrand, Nicolas; Desfourneaux, Véronique; Rahili, Amine; Duffas, Jean-Pierre; et al.
Abstract : Objective: To determine the risk factors of morbidity after surgery for ileocolonic Crohn disease (CD). Summary Background Data: The risk factors of morbidity after surgery for CD, particularly the role of anti-TNF therapy, remain controversial and have not been evaluated in a large prospective cohort study. Methods: From 2013 to 2015, data on 592 consecutive patients who underwent surgery for CD in 19 French specialty centers were collected prospectively. Possible relationships between anti-TNF and postoperative overall morbidity were tested by univariate and multivariate analyses. Because treatment by anti-TNF is possibly dependent on the characteristics of the patients and disease, a propensity score was calculated and introduced in the analyses using adjustment of the inverse probability of treatment-weighted method. Results: Postoperative mortality, overall and intra-abdominal septic morbidity rates in the entire cohort were 0%, 29.7%, and 8.4%, respectively; 143 (24.1%) patients had received anti-TNF <3 months prior to surgery. In the multivariate analysis, anti-TNF <3 months prior to surgery was identified as an independent risk factor of the overall postoperative morbidity (odds-ratio [OR] =1.99; confidence interval [CI] 95% = 1.17–3.39, P = 0.011), with preoperative hemoglobin <10 g/dL (OR = 4.77; CI 95% = 1.32–17.35, P = 0.017), operative time >180 min (OR = 2.71; CI 95% = 1.54–4.78, P < 0.001) and recurrent CD (OR = 1.99; CI 95% = 1.13–3.36, P = 0.017). After calculating the propensity score and adjustment according to the inverse probability of treatment-weighted method, anti-TNF <3 months prior to surgery remained associated with a higher risk of overall (OR = 2.98; CI 95% = 2.04–4.35, P <0.0001) and intra-abdominal septic postoperative morbidities (OR = 2.22; CI 95% = 1.22–4.04, P = 0.009). Conclusions: Preoperative anti-TNF therapy is associated with a higher risk of morbidity after surgery for ileocolonic CD. This information should be considered in the surgical management of these patients, particularly with regard to the preoperative preparation and indication of temporary defunctioning stoma.